2019
DOI: 10.1590/0102-311x00008418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and environmental impact factors of somatization tendencies in eastern Chinese adolescents: a multicenter observational study

Abstract: The aim of this study is at examining the prevalence and impact factors of adolescent somatization tendencies (ST) across three eastern Chinese provinces. A multicenter school-based cross-sectional study was conducted in these provinces from 2015 to 2016. The sample included 11,153 middle-school students aged 13-18 years, who were randomly selected using a multi-phase stratified cluster sampling technique. We also designed a multicenter school-based case-control study to evaluate the potential environmental im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(65 reference statements)
2
7
2
Order By: Relevance
“…This study revealed Chinese adolescents' tendency to express depression through somatic symptoms instead of psychological distress symptoms. This unique conception of depression has been consistently observed in other empirical studies in Chinese adult samples [3][4][5] and adolescent samples [6]. This observation can be explained in terms of the argument that somatization is more acceptable for expressing distress by the Chinese culture, which is precisely described in the Chinese proverb that "man can shed blood but not tears" [42].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This study revealed Chinese adolescents' tendency to express depression through somatic symptoms instead of psychological distress symptoms. This unique conception of depression has been consistently observed in other empirical studies in Chinese adult samples [3][4][5] and adolescent samples [6]. This observation can be explained in terms of the argument that somatization is more acceptable for expressing distress by the Chinese culture, which is precisely described in the Chinese proverb that "man can shed blood but not tears" [42].…”
Section: Discussionsupporting
confidence: 70%
“…Tung [43] proposed a linguistic explanation that many Chinese terms describing negative emotional experience are related to body pain, and thus, the Chinese population may spontaneously use somatic descriptors to express depressed emotions. Additionally, somatization is often observed among adolescents [6]. This may be due to the fact that adolescents' abilities to verbalize emotional distress are not yet fully developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels observed in this investigation are also far beyond those observed by Kihlstrom et al in the total population 45 . The yields in this investigation were also higher compared to our earlier similarity observations 34 , 46 .…”
Section: Discussioncontrasting
confidence: 57%
“…Numerous studies have shown that adolescent DSs (ADSs) could produce several serious adverse referrals, including ADD, narrative disorders, anxiety and depressive disorders, bulimia, attention-de cit/hyperactivity disorder, and suicide [12,13]. Additionally, prior studies have indicated that there were many prominent gender differences in somatization tendencies and hysterical tendencies [14][15][16]. However, we do not yet know if the impact factors of ADSs have the gender difference.…”
Section: Introductionmentioning
confidence: 99%